Comparative Analysis of Primary Prostate Cancer Treatment and Subsequent Metastatic Disease - Shahait, Mohammed; Hamieh, Nadine; Dobbs, Ryan W.; Nguyen, Tuan; Alshannaq, Hamzeh; Kim, Jessica; El-Fahmawi, Ayah; Lee, Daniel J.; Lee, David I. (Frontiers in Urology, 2022)
Objective: To compare the association between previous local treatment modalities and the progression to castrate-resistant prostate cancer (CRCP) and overall survival (OS) in men with newly diagnosed metastatic prostate cancer. Methods: We conducted a retrospective analysis using a nationwide, de-identified electronic health record (EHR)-derived database (Flatiron). Eligible patients had previously received radiation therapy (RT) or radical prostatectomy (RP) for their local disease, and had progressed to metastatic disease. Stratified Kaplan-Meier estimates by local treatment were used to measure OS from the date of metastasis diagnosis. Cox proportional models were used to test the association between prior local treatment, progression to CRPC, and death, after adjusting for patient-and disease-specific parameters. Also, we conducted a propensity score-matched analysis. Results: Of the 1,338 patients who met the inclusion criteria, 46% underwent RP with or without adjuvant RT and 54% received RT. Median follow up for RP group and RT group were 38.6 months (32.6-45.4) and 26.0 months (I24.3-29.9), respectively. After adjusting for patient-and disease-specific parameters, the patients who received RT had a higher risk of developing CRPC than those in the RP group 1.36 [1.05-1.76]. After propensity score matching and adjusting for patient and disease-specific parameters, men who received RT had higher risk of death compared to their counterparts (HR:1.36, 95% CI:1.1-1.65, P= 0.003) Conclusion: Real-world data suggest that patients with metastatic disease who had undergone prior RP might have a lower risk of developing a castrate-resistant state and improved OS compared to patients who had received RT. Significant amount of bias limits validity and strength of our findings. Whether type of local treatment influence the disease behavior remains open question and should be answered only within randomized trial.